A Tale of Two Sites: On Defining the Carrier Concentration in Garnet‐Based Ionic Conductors for Advanced Li Batteries. Issue 11 (21st March 2015) - Thompson, Travis; Sharafi, Asma; Johannes, Michelle D.; Huq, Ashfia; Allen, Jan L.; Wolfenstine, Jeff; Sakamoto, Jeff
<x xml:space="preserve">Abstract</x> Solid electrolytes based on the garnet crystal structure have recently been identified as a promising material to enable advance Li battery cell chemistries because of the unprecedented combination of high ionic conductivity and electrochemical stability against metallic Li. To better understand the mechanisms that give rise to high conductivity, the goal of this work is to correlate Li site occupancy with Li‐ion transport. Toward this goal, the Li site occupancy is studied in cubic garnet as a function of Li concentration over the compositions range: Li7−xLa3Zr2−xTaxO12 (x = 0.5, 0.75, and 1.5). The distribution of Li between the two interstitial sites (24d and 96h) is determined using neutron and synchrotron diffraction. The bulk conductivity is measured on >97% relative density polycrystalline specimens to correlate Li‐ion transport as a function of Li site occupancy. It is determined that the conductivity changes nonlinearly with the occupancy of the octahedral (96h) Li site. It is shown that the effective carrier concentration is dependent on the Li site occupancy and suggests that this is a consequence of significant carrier–carrier coulombic interactions. Furthermore, the observation of maximum conductivity near Li = 6.5 mol is explained.